Questioning evidence-based practice in physiotherapy: a philosophical reflection. The example of physiotherapy with musicians - Rousseau, Céleste; Stiegler, Barbara (Frontiers in Psychology, 2024)
Introduction In the late 1990s, evidence-based medicine (EBM) emerged, emphasizing the conscientious use of current best evidence in medicine and ensuring the best care for each individual. Thus, applying evidence-based practice (EBP) in physiotherapy is complex due to sparse research, distinct challenges, and unsuitable tools. This is particularly relevant considering musicians’ health since the literature is very limited. Part I The first part advocates for EBP and explain how it ensures both the best care and adherence to ethical principles (beneficence, non-maleficence, respect for autonomy, and justice), for both caregivers and patients. Part II The second part discusses the common pitfalls often encountered by healthcare professionals, and especially as physiotherapists for musicians, when applying evidence at the patient’s bedside, again from both perspectives, healthcare professionals and patients. Part III Finally, this third part aims to open the discussion by considering various perspectives, such as values-based practice or the importance of qualitative research, to reshape EBP in physiotherapy. Conclusion This work highlights the prevalent existence of grey zones encountered by healthcare practitioners with musicians. While conducting more research to help understand them, physiotherapists must learn to navigate these waters.